A novel amplified double-quenching aptasensor for cocaine detection based on split aptamer and silica nanoparticles. Issue 26 (22nd June 2018) - Abnous, Khalil; Danesh, Noor Mohammad; Ramezani, Mohammad; Taghdisi, Seyed Mohammad; Emrani, Ahmad Sarreshtehdar
Abstract : Herein, a sensitive and rapid fluorescent aptasensor was developed for the detection of cocaine as an illicit drug, based on an amplification strategy involving the use of silica nanoparticles coated with streptavidin (SNPs), double quenching of FAM fluorophore and cocaine split aptamer. Abstract : Herein, a sensitive and rapid fluorescent aptasensor was developed for the detection of cocaine as an illicit drug, based on an amplification strategy involving the use of silica nanoparticles coated with streptavidin (SNPs), double quenching of FAM fluorophore and cocaine split aptamer. Presence of cocaine could trigger the formation of the double-fragment cocaine aptamer and bring TAMRA fluorophore near the SNP surface and FAM close to BHQ-1 and TAMRA, resulting in the enhancement of relative fluorescence signal (fluorescence intensity of TAMRA/fluorescence intensity of FAM). Under optimal conditions, the proposed aptasensor achieved a limit of detection (LOD) of 84 pM and a linear range of 500 pM to 80 nM for cocaine. The practical potential of the developed sensing platform was proved by the detection of cocaine in spiked human serum samples with satisfactory recoveries.